Will the DAX 50 ESG Establish the Standard for German Sustainable Investments? A Sustainability and Financial Performance Analysis - Martin Nerlinger (Credit and Capital Markets – Kredit und Kapital, 2020)
The demand for sustainable investments is growing worldwide. As a result, the DAX 50 ESG was introduced in March 2020 as the first ESG index by the German stock exchange. It is promoted as the new standard for German sustainable investments. We are the first to comprehensively examine the financial and non-financial performance of the index and its constituents. Therefore, we examine the sustainability performance using both ESG criteria and the alignment of products and services with the Sustainable Development Goals. Our results show that the DAX 50 ESG may only to a limited extent be promoted as the most sustainable German index. Moreover, since inception as well as during the COVID-19 crisis, the DAX 50 ESG's financial performance is comparatively worse. Our findings suggest that stock markets penalize the inclusion of a firm in the DAX 50 ESG in the short run, thus affecting the overall index performance. Our analysis of the DAX 50 ESG further increases investor attention to sustainable financial products and enables better investment decisions.
Keywords: G15; G34; Q56; G11; 330; ESG Disagreement; Event Study; Sustainable Finance; Equity Indices; Sustainability Performance; Financial Performance; ESG; SDG